Role of Extracellular ATP in Cell Fate Determination - Scodelaro Bilbao, Paola; Katz, Sebastian; Boland, Ricardo (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Adenosine 5'-Triphosphate (ATP) is released from cells acting as an extracellular signaling molecule in an autocrine or paracrine manner. ATP and other nucleotides bind to the plasma membrane P2 family of purinergic receptors resulting in the activation of downstream signaling pathways involved in mitogenesis, differentiation and apoptosis. Thereby, they may have a role in the determination of cell fate. This review focuses on the signal transduction cascades activated by ATP and other nucleotides. In particular, we discuss the mitogen activated protein kinase family (MAPK) and phosphatidyl-inositol 3 kinase (PI3K)/Akt pathways and their involvement in the regulation of cell proliferation, differentiation and apoptosis.
Keywords: Apoptosis